Full recovery of muscle function after delayed primary repair of deltoid muscle detachment - (:unkn) unknown (MEDKNOW PUBLICATIONS & MEDIA PVT LTD, 2008)
Detachment of the deltoid muscle and tendon is a rare complication that is reported to result in poor outcome after rotator cuff surgery. We performed a delayed primary repair of the detached deltoid in a 53-year-old female patient who underwent an open acromioplasty procedure. A successful result was achieved after surgical restoration of the deltoid muscle origin back to the acromion. At 25 months follow-up the patient had recovered almost the full range of motion of the glenohumeral joint and was free of pain. Due to lack of literature on this rare condition, there are no well-defined treatment principles for the management of deltoid muscle detachments that develop as a complication of rotator cuff surgery. This paper describes a repair procedure for the management of deltoid muscle detachments. In addition, it discusses the importance of the guidelines that have to be followed during primary rotator cuff surgery.
Keywords: Delayed repair; deltoid; muscle; rupture